Registration of Pyramicocephalus phocarum pl. (Fabricius, 1780) Monticelli, 1890 in pacific capelin Mallotus catervarius (Pennant, 1784) from the coast of West Sakhalin - E. V. Frolov; S. V. Novokreschennykh; N. K. Zavarzina (Известия ТИНРО)
The first case of Pyramicocephalus phocarum pl. parasitism on pacific capelin Mallotus catervarius is registered.